2016
DOI: 10.1039/c6py01445c
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Lewis acid complexation on type I radical photoinitiators and implications for pulsed laser polymerization

Abstract: In the present work, we examine the effects of zinc chloride (ZnCl2) and aluminium chloride (AlCl3) complexation on the photochemistry of two well-known Type I photoinitiators, methyl-4ʹ-(methylthio)-2-morpholinopropiophenone (MMMP) and 2,2-dimethoxy-2-phenylacetophenone (DMPA). High-level ab initio calculations and experimental results demonstrate that Lewis acid complexation has a significant effect on the individual processes that comprise radical photoinitiation. Theoretical calculations predict that ZnCl2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 71 publications
3
44
0
Order By: Relevance
“…As the photoinitiators 2,2-dimethoxy-2-phenylacetophenone (DMPA) and 2-methyl-4-(methylthio)-2-morpholinopropiophenone (MMMP) interact with AlCl3 and ZnCl2 via complexation at the carbonyl in solution, 20 optimization of the PLP conditions was not straightforward and many of our initial samples failed to meet IUPAC consistency criteria and were not included here It was found that in general the presence of LAs resulted in a "smearing" of the MWD as seen in Figure 1. This was particularly a problem in our PLP experiments at higher pulse rates, which also had a greater tendency to yield molecular weight distributions (MWDs) with no secondary inflection points.…”
Section: Optimisation Of Pulsed-laser Polymerisation Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…As the photoinitiators 2,2-dimethoxy-2-phenylacetophenone (DMPA) and 2-methyl-4-(methylthio)-2-morpholinopropiophenone (MMMP) interact with AlCl3 and ZnCl2 via complexation at the carbonyl in solution, 20 optimization of the PLP conditions was not straightforward and many of our initial samples failed to meet IUPAC consistency criteria and were not included here It was found that in general the presence of LAs resulted in a "smearing" of the MWD as seen in Figure 1. This was particularly a problem in our PLP experiments at higher pulse rates, which also had a greater tendency to yield molecular weight distributions (MWDs) with no secondary inflection points.…”
Section: Optimisation Of Pulsed-laser Polymerisation Conditionsmentioning
confidence: 99%
“…The reason for these problems is the interaction between the photoinitiator and Lewis acid, which alters the UV-Vis spectrum by relatively stabilizing the π-π* transitions, and destabilizing the nπ* transitions that lead to homolysis. 20 The net result is a decrease in the initiation rate and an increase in the triplet lifetimes, which becomes problematic at low initiator concentrations and high flashing rates.…”
Section: Optimisation Of Pulsed-laser Polymerisation Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 In a similar vein, complexation with Lewis acids has been shown to dramatically alter the photochemical behavior of photoinitiators, blue shifting the nπ* excitations of type I photoinitiators, methyl-4 0 -(methylthio)-2-morpholinopropiophenone (MMMP) and 2,2dimethoxy-2-phenylacetophenone (DMPA), while concurrently red shifting the ππ* transitions. 10 Even when direct conjugation is not possible, the electrostatic effect of charged functional groups can also influence the relative energies of excited states due to their different polarities. Recently Hill and Coote showed used TD-DFT that by including these charged functional groups as nonconjugated substituents, simple pH changes can be used to selectively modify the relative energies (and even ordering) of the nπ* and ππ* states of an acetophenone derivative.…”
Section: Other Environmental Effectsmentioning
confidence: 99%